Entrepreneurship Business Plan- Healthy Prepared Food Greentox - KO, YUEH NING (2016)
Greentox, a healthy prepared food delivery service, was founded in the summer of 2016, in Taipei, the capital of Taiwan.Greentox was founded on the belief that when we respect our body by caring about what we eat, in turn our body gives us energy and happiness. Greentox offers healthy meals with local and sustainable real food that will help people stay healthy and get rid of toxins from the environments caused by modern life.